Systemic risks perspectives of Eyjafjallajökull volcano's 2010 eruption - Kelman, Ilan; Alexander, David; Fearnley, Carina; Jenkins, Susanna; Sammonds, Peter (Elsevier BV, 2023)
In 2010, southern Iceland's Eyjafjallajökull volcano erupted, releasing ash that spread across Europe. Due to its potential to damage aircraft, much of European airspace was closed for six days. Known problems were brought to the forefront regarding the anticipation of and response to systemic risks. To contribute a deeper understanding of this situation, this paper explores this disaster through its fundamental causes and cascading impacts, highlighting perspectives from disaster risk reduction, complexity sciences, and health in order to support analysis and resolution of systemic risks. Two principal future directions emerge from this work. First, how to manage dependency on air travel. Second, how to think about and act to avert future calamities.